C-reactive protein and coronary atheroma regression following statin therapy: A meta-regression of randomized controlled trials - Gao, Darui; Hua, Rong; Jiesisibieke, Dina; Ma, Yanjun; Li, Chenglong; Wu, Sijing; Ma, Qian; Xie, Wuxiang (Frontiers in Cardiovascular Medicine, 2022)
Objective: Several clinical trials have indicated that statins stabilize and reverse atherosclerotic plaque. However, different studies have provided inconsistent findings regarding mechanisms and influencing factors of plaque regression under statin therapy. In this study, meta-analysis and meta-regression were used to determine the effects of statin medications on coronary plaque volume. Meanwhile, the impact of CRP/hsCRP reduction during statin therapy on plaque regression was investigated. Methods: Up to June 15, 2022, a systematic PubMed, EMBASE, and Cochrane search was performed for randomized controlled trials that assessed treatment effect using total atheroma volume (TAV), percent atheroma volume (PAV), or plaque volume (PV). Only CRP/hsCRP and LDL-C values reported before and after treatment were considered. Results: 12 studies fulfilled the inclusion criteria and were included in the systematic review. A meta-analysis of 15 statin-treated arms reported a significant reduction in change of TAV/PV (standardized mean difference [SMD]: -0.27, 95% confidence intervals [CI]: -0.42, -0.12), compared with the control arms. Another meta-analysis of 7 trials also found that patients in the intervention group had a significant reduction in change of PAV (SMD: -0.16, 95% CI: -0.29, -0.03), compared with those in the control group. Meta-regression analysis revealed the percent change of CRP/hsCRP statistically influences SMD in change of TAV/PV after adjusting for percent change of LDL-C, age and gender. Meta-regression analysis showed that percent change of CRP/hsCRP statistically influences SMD in change of PAV. Conclusion: In conclusion, statin therapy is beneficial for plaque regression. Statins promote plaque regression through their anti-inflammatory ability.